Kinerja Karyawan PT. Multi Karya Asia Pasifik Raya dipengaruhi oleh Gaya Kepemimpinan dan Motivasi Kerja melalui Kepuasan Kerja - Partogi Soloan Samosir; Diana Patrecia Magdalena (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
This study aims to analyze the influence of leadership style and work motivation on employee performance through job satisfaction at PT. Multi Karya Asia Pasifik Raya (MKAPR). The method used in this study is a quantitative method with a descriptive and verification approach. The research sample in this study employees of PT. Multi Karya Asia Pasifik Raya. Data analysis used path analysis. The results of the study indicate that: 1) Leadership style and work motivation influence employee performance through job satisfaction; 2) Leadership style supports improved employee performance; 3) Work motivation supports improved employee performance; 4) Leadership style supports improved job satisfaction; 5) Job satisfaction supports improved employee performance; 6) Leadership style supports improved employee performance through job satisfaction; and 7) Work motivation supports improved employee performance through job satisfaction